Unearthing the global, regional, and national epidemiological landscapes of high BMI-driven ischemic heart disease burden in youth: Trends, determinants, and future trajectories - Kejie He; Haitao Wang (PLoS ONE, 2026)
Background Cardiovascular diseases, including ischemic heart disease (IHD), are leading causes of mortality and morbidity worldwide. High body mass index (BMI) is a major contributing factor. This study aimed to comprehensively analyze the geographic distribution, socioeconomic trends, and age-period-cohort effects of the IHD burden attributable to high BMI to inform targeted interventions. Methods Researchers utilized data from the Global Burden of Disease Study 2021 (GBD 2021) to examine the mortality, incidence, and disability-adjusted life years (DALYs) of IHD related to high BMI among 20–49 year-olds across 204 countries and territories. Joinpoint regression, age-period-cohort modeling, and decomposition analyses were employed to assess the heterogeneous epidemiological patterns across sociodemographic contexts. Results The findings revealed stark geographical disparities, with Central America, the Caribbean, North Africa, and parts of the Middle East and Southeast Asia experiencing the most pronounced IHD burden. Across socioeconomic levels, low sociodemographic index (SDI) countries exhibited persistent increases, while high-middle and high SDI nations showed signs of stabilization or decline. The age-period-cohort analysis uncovered heterogeneous patterns, with the epidemiological transition progressing more rapidly in lower-SDI settings. Decomposition analysis indicated that epidemiological changes and population growth were the dominant drivers of the rising burden in less developed regions. Conclusions This comprehensive analysis elucidates the geographic distribution and socioeconomic differences in the IHD burden attributable to high BMI, providing crucial evidence to guide the development of tailored public health interventions. Context-specific strategies are needed to address the persistent upward trends in resource-limited settings while consolidating the gains made in more developed countries to achieve equitable and sustainable cardiovascular health improvements.